2021
DOI: 10.21203/rs.3.rs-209208/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regorafenib combined with transarterial chemoembolization for unresectable hepatocellular carcinoma: a real world study

Abstract: Background: The benefits and tolerability of transarterial chemoembolization (TACE) combined with regorafenib as a second-line therapy has not been reported for unresectable hepatocellular carcinoma (HCC). To explore the benefits and tolerability of TACE combined with second-line regorafenib in patients with unresectable advanced HCC and failure to first-line treatment.Methods: This was a multicenter retrospective study of patients with progression after first-line sorafenib and/or lenvatinib between 01/2019 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A study reported that the combination of regorafenib and TACE can improve the RPFS of HCC patients. In patients treated with regorafenib combined with TACE, the median RPFS can reach 9.1 months, and the median ROS can reach 14.3 months (19). In addition, a previous study has reported that regorafenib results in an anti-tumor immune response for other cancers (20).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that the combination of regorafenib and TACE can improve the RPFS of HCC patients. In patients treated with regorafenib combined with TACE, the median RPFS can reach 9.1 months, and the median ROS can reach 14.3 months (19). In addition, a previous study has reported that regorafenib results in an anti-tumor immune response for other cancers (20).…”
Section: Discussionmentioning
confidence: 99%
“…Real world data confirmed sorafenib sequential to regorafenib was safe and effective in the treatment of HCC (6,7). Current studies also confirm TACE combined with sorafenib or regorafenib improves the efficacy of therapy (8,9).…”
Section: Introductionmentioning
confidence: 60%
“…Regorafenib is recommended as a third-line treatment for patients with unresectable CRLM and beyond [24]. Mechanistically, the combination of TACE and Regorafenib has complementary efects and can compensate for the problems posed by the rise in VEGF levels after TACE [25]. Although some studies have reported that TACE combined with Regorafenib was more efective in patients with CRLM than Regorafenib alone [26], there has been no comparative study between TACE + Regorafenib and TACE alone in the treatment of CRLM.…”
Section: Introductionmentioning
confidence: 99%